Efficacy prediction of systemic immune-inflammation index and prognostic nutritional index in breast cancer patients and their variations after neoadjuvant chemotherapy - Ni, Jingyi; Qi, Xue; Jin, Conghui; Xu, Weiwei; Li, Xinghui; Song, Li; Zhang, Xunlei (Frontiers in Immunology, 2025)
ObjectiveThe purpose of this study was to evaluate the predictive values of systemic immune-inflammatory index (SII), prognostic nutrition index (PNI), change of SII (ΔSII), change of PNI (ΔPNI) and ΔPNI-ΔSII score in patients with neoadjuvant chemotherapy for breast cancer.MethodsWe enrolled in a retrospective study involving 72 patients with breast cancer between February 2020 and January 2022. All patients had clinical features of axillary lymph node metastasis and received neoadjuvant therapy. PNI and SII were detected by hematology before and after treatment. Chi-square test was used to compare the clinicopathological and experimental parameters among all groups. Logistic regression analysis was used to evaluate the prognostic value of each factor.ResultsThe prognosis was evaluated and 18 patients (25%) achieved pathological complete response (pCR) after neoadjuvant therapy. The pCR rate of breast cancer patients was significantly correlated with ER, PR, HER-2, molecular subsets, tumor size, vascular invasion, nerve invasion, N stage, clinical stage and chemotherapy regimen. Low ΔPNI, high ΔSII and higher ΔPNI-ΔSII score values had better prediction of therapeutic effect, especially the ΔPNI-ΔSII score.ConclusionIn breast cancer patients receiving neoadjuvant chemotherapy, ΔPNI-ΔSII score is an effective predictor of efficacy, which helps to identify high-risk groups and evaluate efficacy.